Faith negotiating loyalties: an exploration of South African Christianity through a reading of the theology of H. Richard Niebuhr - Martin, Stephen William (Department of Religious Studies, 2026)
The context of this thesis is Christian faith in South Africa and the question of loyalties in the new, post-apartheid state. It carries out its investigation in two parts. Part one examines Christian faith and loyalty during the first nation-building exercise following the South African War, positing the creation and contestation of three Christianities corresponding to three nationalisms: South African nationalism, Afrikaner nationalism and African nationalism. Each of these nationalisms imagined South Africa in a certain way, and shaped faith accordingly. Hence the idea of South African Christianity gives way to contesting and contested Christianities, in the same way as nationalism gives way to nationalisms. Faith also emerged in tension with and in criticism of these loyalties. Part two reads H. Richard Niebuhr in South Africa. Three kinds of faith in his writings which are distinguishable in the examination of loyalties in South Africa are set forth: social faith, radical faith and reconstructing faith. The emergence of these understandings of faith in his writings is chronicled by examining five of his major writings: The Social, Sources of Denominationalism, The Kingdom of God in America, The Meaning of Revelation, Christ and Culture, and Faith on Earth. Reference is also made to Radical Monotheism and Western Culture, as well as several important transitional works in the 1930s. The interplay between radical faith and social faith is brought out, as is the idea of reconstructing faith which emerges in the 1950s. Reconstructing faith provides the link again with South Africa, and this is made apparent in an extended conclusion to chapter nine which is also a resume of the exposition of Niebuhr's works, and in the conclusion to the thesis. The self and the society is not the unity that Niebuhr held, but rather is constituted by hybridities and suspended in a web of loyalties. The message for faith in a post-apartheid South Africa that this reading suggests is the importance of negotiating covenants which allow for crossings, hybridities and contestations. Hence the title of this thesis: faith negotiating loyalties.